1985
DOI: 10.2307/3430002
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Free Radicals from Chlorpromazine and Related Phenothiazines: Relationship to Phenothiazine-Induced Photosensitization

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
1
30
0
1
Order By: Relevance
“…Our study provides evidence for this structure as follows. (1) As reported for CPZ [14], the ability of Fraction i to generate radicals (Figure 4a) would be partly due to the residual chloride function. In this study, we observed oligomers with one chlorine atom.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our study provides evidence for this structure as follows. (1) As reported for CPZ [14], the ability of Fraction i to generate radicals (Figure 4a) would be partly due to the residual chloride function. In this study, we observed oligomers with one chlorine atom.…”
Section: Discussionmentioning
confidence: 98%
“…These results suggest that the inhibitory substance(s) in this fraction still have the ability to generate radicals on UV irradiation, although the radical(s) derived from Fraction i are not identical to the radical(s) derived from CPZ. The inhibitory substance might be apt to release an electron when irradiated, or possess a chloride function that is probably cleaved upon irradiation to generate radicals, as reported for the chloride function at position 2 of the CPZ molecule [14]. Since a trace amount of radical was observed in the EPR spectrum of Fraction i, we investigated whether radical(s) were directly involved in the inhibition by examining the effect of a radical scavenger, ascorbate, on the inhibition of the enzymatic activity.…”
Section: Epr Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon UV irradiation CPZ produces a variety of free radicals along with the corresponding cation radical, the neutral promazinyl radical, a chlorine radical and super-centered peroxy radical. The neutral promazinyl radical can react covalently with cell membrane, protein, and other macromolecules to yield antigens which could be responsible for the photoallergic response to CPZ resulting phototoxicity, both in vitro and in vivo [38]. Hence, CPZ was used as a positive control in the current study and as expected exhibited the highest cytotoxic and phototoxic activity on HaCaT cell among all surfactant tested.…”
Section: Discussionmentioning
confidence: 99%
“…4) Schizophrenia is one of the major diseases treatable by CPZ, and its mechanism of action is thought to be antagonistic effect on the dopamine D2 receptor. 5) As CPZ was widely used, its photo-toxic and photo-allergic adverse effects were also reported 6) ; therefore, its photo-degradation reaction has been intensely studied. [7][8][9][10][11] In the previous studies, the main focus was on structures and bioactivities of monomeric derivatives that were generated via photo-irradiation of CPZ.…”
mentioning
confidence: 99%